Allogeneic hematopoietic cell transplantation for primary refractory acute lymphoblastic leukemia: A report from the Acute Leukemia Working Party of the EBMT. Issue 11 (17th February 2017) - Pavlů, Jiří; Labopin, Myriam; Zoellner, Anna K.; Sakellari, Ioanna; Stelljes, Matthias; Finke, Jürgen; Fanin, Renato; Stuhler, Gernot; Afanasyev, Boris V.; Bloor, Adrian J.; Anagnostopoulos, Achilles; Mohty, Mohamad; et al.
Abstract : BACKGROUND: Patients with primary refractory acute lymphoblastic leukemia (PREF ALL) who fail to achieve a complete remission (CR) after ≥2 courses of chemotherapy have a dismal prognosis without undergoing allogeneic hematopoietic cell transplantation (HCT). To the authors' knowledge, there currently are no data regarding factors influencing transplantation outcomes. METHODS: The authors retrospectively studied outcomes of transplantation for cases of PREF ALL reported to European Society for Blood and Marrow Transplantation registry. Eligibility criteria for the current analysis included adult patients who underwent their first HCT for PREF ALL between 2000 and 2012. PREF disease was defined as the failure to achieve a morphological CR after ≥2 courses of induction chemotherapy. RESULTS: Data regarding 86 adult patients were analyzed. With a median follow‐up of 106 months, the probability of survival was 36% at 2 years and 23% at 5 years. The probability of leukemia‐free survival was 28% and 17%, respectively, and the probability of nonrecurrence mortality was 20% and 29%, respectively, at 2 years and 5 years. For 66 patients who achieved a CR (77%), the survival at 2 years and 5 years was 36% and 29%, respectively. In multivariate analysis, use of total body irradiation was found to be associated with improved survival. Total body irradiation and infusion of female hematopoietic cells into male recipients was associated with improved leukemia‐free survival. These findings were incorporated into a scoring system that identified 3 groups (those with 2, 1, or no prognostic factors) with survival rates of 57%, 22%, and 8%, respectively. CONCLUSIONS: Although overall these patients would clearly benefit from the introduction of novel antileukemic therapies, the data from the current study support the use of allogeneic HCT in selected patients with PREF ALL. Cancer 2017;123:1965–1970 . © 2017 American Cancer Society . Abstract : The objective of the current study is to establish the outcomes of allogeneic hematopoietic cell transplantation in patients with primary refractory acute lymphoblastic leukemia and to identify factors potentially influencing these outcomes. With a median follow‐up of 106 months, the probability of survival is reported to be 36% at 2 years and 23% at 5 years, with superior survival noted among patients who received total body irradiation and in male patients receiving hematopoietic cells from female donors.